Project and Development of ErgoCoIn Version 2.0 - Morandini, Marcelo [UNESP]; de Moraes Rodrigues, Roberto Leite [UNESP]; Cerrato, Marcus Vinicius [UNESP]; Chaim, Marcos Lordello [UNESP] (Springer-verlag Berlin, 2011)
Usability evaluation (UE) methods may have several purposes: identify and diagnose usability problems; evaluate the implementation, comparing the one under evaluation with other systems, and also perform acceptance test. These methods are usually expensive, time-consuming and complex. In this context, the ErgoCoIn 1.0 has being used as an accessible system that can be used by several people all over the world, even if they are not usability experts or evaluators. This paper aims to present a new version of this environment considering that its basic objective is to propose a higher quality for the questions. Additionally, a new presentation questionnaire window small enough to be used both in web browsers and mobile devices is proposed.
Keywords: Usability Evaluation; Checklist; Automation